The concurrent treatment of Scutellaria baicalensis Georgi enhances the therapeutic efficacy of cisplatin but also attenuates chemotherapy-induced cachexia and acute kidney injury. (28th October 2019) - Huang, Tse-Hung; Wu, Tsung-Han; Guo, Yi-Hui; Li, Tsung-Lin; Chan, Yi-Lin; Wu, Chang-Jer
Abstract: Ethnopharmacological relevance: Cisplatin is an important chemotherapy to lung cancer, but it usually induces severe cachexia and acute kidney injury in patients. Scutellaria baicalensis Georgi (SB), commonly known as a skullcap, is a popular Chinese herbal medicine mainly used to treat inflammation, infection, and malignancy. In this study, we report the synergic effect of SB and cisplatin to Lewis lung carcinoma (LLC) cells, and the ameliorative effect of SB to cisplatin-induced cachexia and acute kidney injury. Materials and methods: The extract of SB was applied by water boiling and lyophilization. The MTS assay was used to exam the in-vitro effects of SB and cisplatin on the LLC viability. In the animal experiment, male C57BL/6J mice were inoculated with LLC cells, and then treated by cisplatin intraperitoneally and the SB extract orally. Tumor volume, weights of tumor, murine body, white adipose tissue and gastrocnemius muscle, as well as serum levels of BUN and creatinine were measured during the experiment. Murine kidney sample was observed after the H&E and annexin V staining. Results: SB provided an enhancement of cisplatin action to inhibit tumor growth in vitro and in vivo. In the animal experiment, SB improved the loss of murine body weight and gastrocnemius muscle, the elevating BUN level, and the apoptosis of renal tubular cells in mice receiving cisplatin therapy. Meanwhile, the current treatment of SB did not further interfere with the blood cell counts of mice receiving chemotherapy. Conclusion: SB can enhance the anti-cancer effect of cisplatin. It also attenuates cisplatin-induced cachexia and acute kidney injury. Graphical abstract: Image 1